Comparative performance on plant morphology and biomass yield of two selected Moringa oleifera cultivars (Bangladesh Journal of Animal Science, 2020)
Moringa (Moringa oleifera) could be one of the promising tree fodders to meet up the seasonal forage shortage in Bangladesh. Two cultivars of Moringa oleifera species namely Black Seed Moringa (BSM-L)  Local and White Seed Moringa (WSM-L) Local were cultivated at fodder research field in Bangladesh Livestock Research Institute (BLRI), Savar, Dhaka, Bangladesh during the period from August 2015 to December 2017 to determine plant morphology and biomass yield in different seasons of two consecutive years under common agronomical practices. The production performances of two Moringa cultivars were analyzed in an ANOVA of a Randomized Block Design (RBD). The result revealed that BSM-L had significantly higher survivability (89.12%, P